Yumuşak Güç Kavramı Çerçevesinde Avrasya Ekonomik Birliği ve Kuşak-Yol İnisiyatifinin Değerlendirilmesi - Göktürk TÜYSÜZOĞLU (Gazi Akademik Bakış)
Without resorting to military power and political coercion measures, soft power, which can be interpreted as influencing or transforming other actors in favor of its own interests, especially in the context of economic/commercial reward mechanisms and cultural or political value transfer process, is one of the most important tools used in international politics. In recent years, China takes striking steps in the use of soft power. Beijing, which aims to use its growing economic power and commercial opportunities as tools of soft power rather than its political values, aims to revive the historical Silk Road under its control. Russia, like China, gives priority to the understanding of systemic multi-polarity and has disagreement with the US in various fields and has recently turned to the use of soft power. While Russia is far behind China in terms of economic power, it has turned to establish a regional hegemony through the Eurasian Economic Union, which it presents as an institutional structure. However, the fact that both initiatives have generally targeted the same geography also leads to a prediction that China and Russia, which co-exist in the context of demand for systemic change in the current conjuncture, may lead to a long-term competitive conflic